Food & drink tourism : principles and practice - Everett, Sally, ....- (Los Angeles : SAGE, 2016)
Dedicated to the growing field of food and drink tourism and culinary engagement, Sally Everett offers a multi-disciplinary approach to the subject informed by many academic fields within the social sciences and business education. It embraces theories and examples from numerous subject disciplines, including tourist studies, tourism management, cultural studies, business, sociology, marketing, geography, event management and hospitality. Critical theory reflections, real-life case studies, student exercises, diagrams, policy documents, media excerpts and activities, examples of food and drink tourism around the world as well as a focus on employability combine to provide a comprehensive & engaging resource on food & drink tourism and food motivated travel & leisure relevant to any student studying tourism, hospitality, events, sociology, marketing, business and cultural studies.
Keywords: Toerisme : eten; Toerisme : drinken; Foodtourism